Pengaruh Penerbangan Militer terhadap On Time Performance (OTP) Penerbangan Regular di Bandar Udara Internasional Husein Sastranegara Bandung - Hasanah, Fatayat Uswatun; Hilal, Raden Fatchul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Every airport must have a flight system, both scheduled (regular) and non-scheduled. In this case it is very important to note that the airport prioritizes customer satisfaction, namely by prioritizing flight timeliness (on time performance ) regular flights. Predetermined timeliness will have an important effect to support the level of customer satisfaction in particular and to maintain passenger loyalty in accordance with the planned marketing targets. This study uses a quantitative descriptive research method. To be able to get answers from this study, researchers used primary data from observations and secondary data from the number of regular and military flights during May to August at Husein Sastranegara International Airport, Bandung. This descriptive quantitative research explains the existing data to determine the sample ratio. The results of the study show that the comparison of the two flights is quite significant, when viewed from the results of the primary observational data that the researchers carried out from several military aviation activities it has quite an effect on regular flights and affects the size ofon time performance regular flights, but when viewed from the results of secondary data, the comparison of the amount of data on regular flights is still higher than military flights. this must still be considered carefully because flight timeliness remains one of the main points in achieving customer satisfaction at the airport. Keywords: Military Aviation,On Time Performance, Regular Flights